2017
DOI: 10.2320/matertrans.m2016312
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocapacitive Behavior of Ag<sub>3</sub>PO<sub>4</sub> Nanospheres Prepared by a Sonochemical Process

Abstract: Ag 3 PO 4 nanospheres with an average size of 300 nm were synthesized via a sonochemical process. The electrochemical performances of the as-synthesized Ag 3 PO 4 nanospheres in aqueous KOH electrolyte with different concentrations were investigated by cyclic voltammetry, galvanostatic charge-discharge and electrochemical impedance spectroscopy. The measured cyclic voltammetry curves as well as charge-discharge curves reveal a good pseudocapacitive behavior of Ag 3 PO 4 nanospheres. In a 1 M KOH electrolyte at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The CV of the catalyst coated GCE revealed a reduction peak at 0 V and an oxidation peak at 0.62 V corresponding to the reduction of Ag + to Ag(0) and Ag(0) to Ag + , respectively (given in eqn (4) and (5)). 53 Ag + + e − → AgAg–e − → Ag + …”
Section: Resultsmentioning
confidence: 99%
“…The CV of the catalyst coated GCE revealed a reduction peak at 0 V and an oxidation peak at 0.62 V corresponding to the reduction of Ag + to Ag(0) and Ag(0) to Ag + , respectively (given in eqn (4) and (5)). 53 Ag + + e − → AgAg–e − → Ag + …”
Section: Resultsmentioning
confidence: 99%
“…[24] Liu et al discovered that the edge of the conduction band of Ag 3 PO 4 is composed of Ag 5 s5p and a small amount of P 3 s orbital, and the edge potential of the valence band top is composed of Ag 4d and O 2p orbital, showing a high oxidation potential of 2.67 eV. [25] Research by Zheng et al indicated that Ag 3 PO 4 displayed a high specific capacity of 832 F g À 1 at 0.5 A g À 1 , [26] meaning that Ag 3 PO 4 has good electronic transfer performance. However, as an excellent potential candidate material for supercapacitors, the specific capacity of Ag 3 PO 4 needs to be further increased.…”
Section: Introductionmentioning
confidence: 99%
“…The composite of Ag3PO4/g-C3N4 [15], Ag3PO4/MoS2 [16], and Ag3PO4-coated carbon microspheres [17] may be designed with the hydrothermal synthesis. Graphene/Ag3PO4 quantum dots [12] and Ag3PO4 nanospheres [18] may be prepared using a sonochemical process. The composites of Ag3PO4/g-C3N4 [19], Ag3PO4/Ag2W2O7 heterojunction [20], and Ag3PO4-graphene [21] may be synthesized using co-precipitation method.…”
Section: Introductionmentioning
confidence: 99%